Educators who believe: understanding the enthusiasm of teachers who use digital games in the classroom - Colleen Stieler-Hunt; Christian M. Jones (Association for Learning Technology, 2015)
This study used qualitative methods to explore why some educators embrace the use of digital game-play (DGP) in the classroom. The results indicated that these teachers had a very strong belief that DGP could be beneficial for learning which stemmed from experiencing their own form of subjective success with using DGP in the classroom, availing themselves of information and advocacy about using DGP in the classroom and personal experiences with DGP either through their own DGP or through watching their own children play games. They also shared positive attitudes towards information and communication technologies generally and had initially been invited to use DGP in the classroom by someone in authority. Their use of DGP was also something that they felt made them different to other teachers. Applying these findings to Rogers' Diffusion of Innovations theory predicted that the diffusion rate of using DGP in the classroom will continue to be slow. Finally, this study indicates that teachers need to experience their own form of subjective 'success' in order to find DGP valuable and this subjective 'success' often goes beyond test score performance.